Sinapic acid impacts the emulsifying properties of rapeseed proteins at acidic pH. (April 2022) - Ntone, Eleni; Qu, Qiyang; Gani, Kindi Pyta; Meinders, Marcel B.J.; Sagis, Leonard M.C.; Bitter, Johannes H.; Nikiforidis, Constantinos V.
Abstract: Extensive purification of plant proteins is probably not a prerequisite for their emulsifying properties, however, details of the interfacial stabilization mechanism of less purified protein extracts are not sufficiently known. Phenolic compounds present in less purified plant protein extracts can interact with proteins, inducing protein aggregation, impeding their interfacial properties. Here, we show that when a rapeseed protein mixture (RPM) containing 40 wt% proteins and 6 wt% sinapic acid is used to form oil-in-water emulsions (10.0 wt% oil) at pH 3.8 and at different protein concentrations (0.2–1.5 wt%), emulsion droplets of 2.0–0.6 μm are formed and large protein aggregates are randomly attached to the droplet interface. By reducing the sinapic acid content to 2.5 wt% to produce a rapeseed protein concentrate (RPC) (65 wt% proteins), smaller emulsion droplets are formed (0.4–0.5 μm) at the same protein concentrations, and no large proteins aggregates are present at the droplet interface. According to our findings, in both RPM- and RPC-stabilized emulsions, napins primarily adsorb at the interface, while cruciferins form a secondary layer which protects the droplets against coalescence during homogenization. However, in RPM, the higher sinapic acid content possibly induces aggregation of cruciferins, which hinders the formation of a sufficient secondary layer. As a result, during homogenization, the colliding droplets coalesce, resulting in emulsions with larger droplets. Our findings show that sinapic acid affects the emulsification mechanism of rapeseed proteins at acidic pH, and recommend that plant protein purification might be necessary for the application of plant proteins in emulsion food products. Graphical abstract: Image 1 Highlights: Less purified rapeseed protein extracts formed stable emulsions at acidic pH. Napins were primarily adsorbed at the oil/water interface. Cruciferins formed a secondary layer, impeding droplet coalescence during homogenization, resulting in smaller emulsion droplets. Sinapic acid induced cruciferin aggregation, hindering the secondary layer formation, resulting in droplet coalescence and larger droplets. Removal of sinapic acid resulted in smaller emulsion droplets.